PERKEMBANGAN KULTUR DAUN Aglaonema sp. var Siam Pearl, Aglaonema sp. var. Lady Valentin dan Aglaonema sp. var. Lipstik DENGAN PERLAKUAN ZAT PENGATUR TUMBUH IAA DAN BAP - Ika Sukma Dewi; Dwi Kusuma Wahyuni; Hery Purnobasuki (The East Java Biological Society, 2012)
The aim of this research was to know the effect of 3-indole-acetic acid (IAA) and 6-bensilaminopurine (BAP) and optimum concentration of IAA+BAP toward growth and development of the leaf culture of Aglaonema sp. var. Siam Pearl, Aglaonema sp. var. Lady Valentine, and Aglaonema sp. var. Lipstik. The explants were taken from the leaf. The explants were cultured in solid MS medium with addition various concentration of IAA 0,5 mg/l, 2 mg/l, 3 mg/l, 5 mg/l, and 8 mg/l and BAP 5 mg/l. Observation had been conducted for 16 weeks to know the response the development of explants leaves such as the periphery of explants coloured of brown, leaves explants of arch shaped, the colour of explants to change for pale, and to form callus. The data were include of the number of explants which able to form callus, time of callus formation, the colour and texture callus, and stage of development explants were analyzed descriptively. The result of 16 weeks observation showed that the addition of IAA and BAP on the leaves explants to give the different effects. Aglaonema sp. var. Lipstik can form callus by treatment of 5 mg/l IAA:5mg/l BAP, and 8 mg/l IAA:5 mg BAP. The colour of callus are clear, the shape of globular, with friable textures.